Qingxin Kaiqiao Recipe Improves Cognitive Performance, Inhibits Apoptosis, and Reduces Pathological Deposits in APP/PS1 Double Transgenic Mice via the PI3K/Akt Pathway. (28th April 2020) - Lin, Shi-Yi; Wang, Tian-Qi; Xu, Lu-Ting; Lai, Xiao-Xiao; Shen, Yan; Lin, Jian-Wei; Gao, Shi-Yu; Hu, Hai-Yan
Abstract : The traditional Chinese medicine of Qingxin Kaiqiao Recipe (QKR) is effective in the treatment of Alzheimer's disease (AD). This study aims to investigate whether QKR improves the cognitive ability and takes neuroprotective effect on APP/PS1 double transgenic mice via the PI3K/Akt pathway. APP/PS1 double transgenic mice were randomly divided into a model, donepezil-treated, or QKR-treated group (L-QKR: 4.75 mg/kg/d, M-QKR: 9.5 mg/kg/d, and H-QKR: 19 mg/kg/d, respectively). Wild-type C57/BL6J mice were used as the control group. Morris water maze (MWM) was used to test the ability of spatial navigation and memorization; terminal deoxynucleotidyl transferase-mediated dUTP nick end-labelling (TUNEL) assay was applied to test the apoptosis; amyloid protein granule deposition was detected via Methenamine silver staining; Western blot (WB) analysis, immunohistochemistry, and RT-PCR were applied to measure the expression of A β and corresponding indicators of the PI3K/Akt pathway. Compared with the model group, QKR significantly relieved the cognitive impairment, reduced the deposition of senile plaques, decreased the expression of GSK-3 α and A β, and increased the expression of p-PI3K, p-Akt, and IDE. In addition, the number of TUNEL-positive cells decreased after treatment using QKR. The current study proved that QKR, especially at the high dose tested, exerted a protective effect on improving learning and memory, inhibiting apoptosis, and reducing the process of pathological degeneration in the hippocampus of AD mice.